Infection-targeted bactericidal nanoparticles. (February 2018) - Li, Li-Li; Wang, Hao
Nanoparticles carrying an antibiotic and bearing a peptide that targets the bacteriumStaphylococcus aureus effectively suppress staphylococcal infections in mice.